Impact of Teacher Training on Performance in English at the Primary Level: An Untold Story of West Bengal - Mandal, Debarshi; Sarkar, Debasish (INDIAN EDUCATIONAL REVIEW, 2017)
Continuous teachers’ training and orientation is an important instrument for quality education at the primary level. This paper attempts to study the impact of teachers’ training programme based on the experience in West Bengal. In West Bengal, a general consensus was developed on the necessity of imparting quality teaching learning of English at the primary level during the beginning of 21st century when English was reintroduced after a long gap of time. As a result, a convergent, coordinated and long-term continuous effort was made with respect to teachers’ training in English. Based on the analysis of performance of the students in External Evaluation (EE) and Diagnostic Achievement Test (DAT) at the end of Classes II and III, respectively, conducted by West Bengal Board of Primary Education (WBBPE), it was observed that only due to the massive training programme, the performance of the students was comparatively better in English as compared to all other subjects.